Evidence for dissolved hydrogen in the mixed ionic–electronic conducting perovskites La0.6Sr0.4FeO3−δ and SrTi0.7Fe0.3O3−δ. Issue 38 (19th September 2016) - Grünbacher, Matthias; Köck, Eva-Maria; Kogler, Michaela; Klötzer, Bernhard; Penner, Simon
Abstract : Evidence for dissolved hydrogen in mixed ionic–electronic conducting A- and B-site substituted perovskites. Abstract : Two mixed ionic–electronic conducting, Fe-containing perovskites were investigated regarding their reducibility in dry H2, namely lanthanum strontium ferrite (LSF4, La0.6 Sr0.4 FeO3− δ ) and strontium titanium ferrite (STF3, SrTi0.7 Fe0.3 O3− δ ). Upon treatment under comparable reduction conditions, LSF4 is by far more affected by reduction and is reduced more deeply than STF3. Thermal treatments of fully oxidized or slightly reduced LSF4/STF3 at decreased O2 partial pressure lead to spontaneous desorption of O2 . Temperature-programmed desorption (TPD) spectra of H2 reveal distinct differences in H2 and H2 O desorption. A simple mass balance of H2 reveals that oxygen vacancies formed on STF3 are more resilient towards O2 re-oxidation compared to those on LSF4. The results also imply that substantial amounts of hydrogen are dissolved in the bulk of LSF4 or STF3. 4.9 × 10 −2 mol H2 per mol LSF4 and 1.6 × 10 −2 mol H2 per mol STF3 are incorporated if the specimens are heated in flowing/dry H2 up to 550 °C and 612 °C, respectively. For LSF4 this equals about 13 hypothetical ML of H2 and for STF3 about 20 hypothetical ML of H2 . This conclusion is also supported by Fourier-transform infrared spectroscopy (FT-IR). FT-IR reveals water formation during static H2 treatment of LSF4/STF3, which indicates perovskite reduction. Furthermore, both samples behave extraordinarily hydrophobic and no chemistry involving surface hydroxy groups was observed.